GAMBARAN PENGETAHUAN BIDAN TERHADAP PROGRAM PENGENDALIAN INFEKSI DI RUMAH SAKIT UMUM DAERAH PANDAN ARANG BOYOLALI - Nining Supriyanti; Putri Kusumawati Priyono; Ika Winarningrum (STIKES DUTAGAMA KLATEN, 2015)
Background: The rate of nosokomial infection in soe countries are between 3,3% to 9,2%, its means that some percents of the patients are infected with nosokomial infection and it could happen chronically and acutely. The Objective: To know the description of midwife knowledge to the infection control program at Pandan Arang Hospital Boyolali Method Of The Study: This is a qualitative research using cross sectional approach. The populations of the research are all midwifes which consist of 30 midwifes. Result: The description of midwife knowledge to the infection control program 17 (56,7%) (less), the definition 30 (100%) (good), the hand cleaness 16 (53,3% ) (less), the body protector 26 (86,7%) (good), desinfection 30 (100%) (exactly), the waste processing is 17 (56,7%) (less), the environment cleansing 17 (56,7%) (exactly), the health staff 17 (56,7%) (exactly), the respiration hygiene 26 (86,7%) (exactly), how to do the injection safety 26 (86,7%) (good), lumbal punksi 29 (96,7%) (exactly). Conclusion: The description of midwife knowledge to the infection control program 17 (56,7%) (less).